Creative Reception of Literary Works: A Research-Creation Model Based on Alice Munro's Short Stories - Pino-Posada, Juan Pablo; Jaramillo-Appleby, Valentina (Íkala, Revista de Lenguaje y Cultura, 2022)
The growing technification of literary studies has made the tools of analytical mediation and argumentative-rational distancing prominent, to the detriment of the emotional and imaginative potential of reading literary pieces. This article provides a model of creative reception that grants greater significance to the subjective involvement of the reader-researcher. The model is inserted in the current Colombian institutional framework of research-creation in literature and mobilizes, for training and research processes of the discipline, the cognitive potential of hypertextual creation and rewriting. This is the result of critical-hermeneutical and creative writing experiments carried out in a research hotbed of a university in Medellín, Colombia. The proposal is based on Wolfgang Iser’s theory of literary reception and on Umberto Eco’s idea of a reader participating in the work and cooperating with the text. It also draws on contemporary contributions to the aesthetics of creation, specifically, on Kenneth Goldsmith’s practice of non-creative writing. Finally, it brings to the table the recent discussion on the relationship between research and creation. Its main contribution of the model is the systematic and collaborative activation of analytical and creative abilities in the reader.